Study of Palm Oil Mill Effluents Treatment Using Bio Engineered Structure Biomedia - Abdul Aziz, Mohd Azoddein; Ahmad Bazli, Bustary; F. A. M., Azli; N. H. Z., Abidin; I. M., Ali; M. S. M., Desa (Malaysian Technical Universities Network (MTUN), 2015)
Palm Oil Mill Effluent (POME) is waste produced by the palm oil processing mills in Malaysia and also generates large quantities of liquid waste. This research is aim to remove high content of suspended solids and oil in POME by using Bio Engineered Structure (BES) bio media. Besides that, it also to investigate condition of BES biomedia for POME treatment in bioreactor system and also the main factors affecting BES biomedia performance in POME treatment. The BES biomedia for POME wastewater treatment system is a compact biological purification system and enhanced the conditions for the microbiology to breakdown the pollution. The nutrient broth mixed with Pseudomonas putida (P. putida) was injected to BES biomedia tank with the ratio of 1:9 P. putida to POME. The growth of P. putida was compared between in shake flask and BES biomedia reactor. In shake flask, the P. putida take a shorter time to encounter with the environment while in BES biomedia reactor it take more period to encounter with a new environment. From the aeration rate, it shows that at rate of one L/min have the highest removal efficiency of Chemical Oxygen Demand (COD), 46.73%, Biochemical Oxygen Demand (BOD), 99.03% and Total Suspended Solids (TSS), 71.88%. As conclusion, BES biomedia is potentially to be a good method to treat POME that will reduce the uncontrolled waste and environmental pollution to our country.